let U be non empty set ; :: thesis: for A, B being non empty IntervalSet of U holds A _\/_ B = Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2)))
let A, B be non empty IntervalSet of U; :: thesis: A _\/_ B = Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2)))
thus A _\/_ B c= Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2))) :: according to XBOOLE_0:def 10 :: thesis: Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2))) c= A _\/_ B
proof
let x be object ; :: according to TARSKI:def 3 :: thesis: ( not x in A _\/_ B or x in Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2))) )
reconsider xx = x as set by TARSKI:1;
assume A1: x in A _\/_ B ; :: thesis: x in Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2)))
then consider X, Y being set such that
A2: ( X in A & Y in B & x = X \/ Y ) by SETFAM_1:def 4;
A3: ( A ``1 c= X & X c= A ``2 ) by ;
A4: ( B ``1 c= Y & Y c= B ``2 ) by ;
then A5: xx c= (A ``2) \/ (B ``2) by ;
(A ``1) \/ (B ``1) c= xx by ;
hence x in Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2))) by A1, A5; :: thesis: verum
end;
thus Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2))) c= A _\/_ B :: thesis: verum
proof
let x be object ; :: according to TARSKI:def 3 :: thesis: ( not x in Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2))) or x in A _\/_ B )
assume x in Inter (((A ``1) \/ (B ``1)),((A ``2) \/ (B ``2))) ; :: thesis: x in A _\/_ B
then consider Z being Element of bool U such that
A6: ( x = Z & (A ``1) \/ (B ``1) c= Z & Z c= (A ``2) \/ (B ``2) ) ;
A ``1 c= (Z \/ (A ``1)) /\ (A ``2)
proof
let x be object ; :: according to TARSKI:def 3 :: thesis: ( not x in A ``1 or x in (Z \/ (A ``1)) /\ (A ``2) )
assume A7: x in A ``1 ; :: thesis: x in (Z \/ (A ``1)) /\ (A ``2)
assume A8: not x in (Z \/ (A ``1)) /\ (A ``2) ; :: thesis: contradiction
end;
then ( A ``1 c= (Z \/ (A ``1)) /\ (A ``2) & (Z \/ (A ``1)) /\ (A ``2) c= A ``2 ) by XBOOLE_1:17;
then A10: (Z \/ (A ``1)) /\ (A ``2) in A by Th14;
B ``1 c= (Z \/ (B ``1)) /\ (B ``2)
proof
let x be object ; :: according to TARSKI:def 3 :: thesis: ( not x in B ``1 or x in (Z \/ (B ``1)) /\ (B ``2) )
assume A11: x in B ``1 ; :: thesis: x in (Z \/ (B ``1)) /\ (B ``2)
then A12: x in Z \/ (B ``1) by XBOOLE_0:def 3;
B ``1 c= B ``2 by Th16;
hence x in (Z \/ (B ``1)) /\ (B ``2) by ; :: thesis: verum
end;
then ( B ``1 c= (Z \/ (B ``1)) /\ (B ``2) & (Z \/ (B ``1)) /\ (B ``2) c= B ``2 ) by XBOOLE_1:17;
then A13: (Z \/ (B ``1)) /\ (B ``2) in B by Th14;
((Z \/ (A ``1)) /\ (A ``2)) \/ ((Z \/ (B ``1)) /\ (B ``2)) = (((Z \/ (A ``1)) /\ (A ``2)) \/ (Z \/ (B ``1))) /\ (((Z \/ (A ``1)) /\ (A ``2)) \/ (B ``2)) by XBOOLE_1:24
.= (((Z \/ (A ``1)) \/ (Z \/ (B ``1))) /\ ((A ``2) \/ (Z \/ (B ``1)))) /\ (((Z \/ (A ``1)) /\ (A ``2)) \/ (B ``2)) by XBOOLE_1:24
.= ((Z \/ ((A ``1) \/ (B ``1))) /\ ((A ``2) \/ (Z \/ (B ``1)))) /\ (((Z \/ (A ``1)) /\ (A ``2)) \/ (B ``2)) by XBOOLE_1:5
.= (Z /\ ((A ``2) \/ (Z \/ (B ``1)))) /\ (((Z \/ (A ``1)) /\ (A ``2)) \/ (B ``2)) by
.= ((Z /\ (A ``2)) \/ (Z /\ (Z \/ (B ``1)))) /\ (((Z \/ (A ``1)) /\ (A ``2)) \/ (B ``2)) by XBOOLE_1:23
.= ((Z /\ (A ``2)) \/ Z) /\ (((Z \/ (A ``1)) /\ (A ``2)) \/ (B ``2)) by
.= Z /\ ((B ``2) \/ ((Z \/ (A ``1)) /\ (A ``2))) by
.= Z /\ (((Z \/ (A ``1)) \/ (B ``2)) /\ ((A ``2) \/ (B ``2))) by XBOOLE_1:24
.= Z /\ ((Z \/ ((A ``1) \/ (B ``2))) /\ ((A ``2) \/ (B ``2))) by XBOOLE_1:4
.= Z /\ ((Z /\ ((A ``2) \/ (B ``2))) \/ (((A ``1) \/ (B ``2)) /\ ((A ``2) \/ (B ``2)))) by XBOOLE_1:23
.= Z /\ (Z \/ (((A ``1) \/ (B ``2)) /\ ((A ``2) \/ (B ``2)))) by
.= Z /\ ((Z \/ ((A ``1) \/ (B ``2))) /\ (Z \/ ((A ``2) \/ (B ``2)))) by XBOOLE_1:24
.= (Z /\ (Z \/ ((A ``1) \/ (B ``2)))) /\ (Z \/ ((A ``2) \/ (B ``2))) by XBOOLE_1:16
.= Z /\ (Z \/ ((A ``2) \/ (B ``2))) by
.= Z by ;
then consider X, Y being Subset of U such that
A14: ( X in A & Y in B & Z = X \/ Y ) by ;
thus x in A _\/_ B by ; :: thesis: verum
end;